Combined deficiency of factor V and factor VIII: management during cardiothoracic surgery. Issue 3 (April 2017) - Howard, Christin; Lipe, Brea
Abstract : N/A: Combined factor V and factor VIII deficiency is an extremely rare bleeding disorder for which research is lacking. We present the case of a 33-year-old man requiring repeat mitral valve replacement. A multidisciplinary team approach was utilized to minimize his risk of bleeding which included the use of plasma exchange, intravenous factor replacement, and platelet transfusion. This approach created an operative experience that did not require blood transfusion or the use of other hemostatic medications.